Exploring the preparedness of hospital pharmacists practising in Southwest London for implementing pharmacogenomics testing - Thuy Mason; Éirne Ní Dheasmhúnaigh; Heba Ghazal (Journal of Pharmaceutical Policy and Practice)
Introduction Pharmacogenomics (PG), the study of how genetic variations impact individual responses to drugs, has seen significant advancements globally in recent years. Hospital pharmacists play a crucial role in multi-disciplinary teams and understanding their preparedness to deliver PG services is essential for successful integration into the healthcare systems. This study evaluates their knowledge, training and seeks their views on PG testing implementation.Methods A cross-sectional study was conducted on hospital pharmacists practising in Southwest London with the sample size determined as 137. The study was ethically approved. A structured, self-administered questionnaire was initially piloted, then distributed using emails with a link to Microsoft Form over a three-month period. It comprised 31 questions covering training levels, confidence, knowledge, perceptions, barriers to implementation and demographics.Results A total of 46 responses were received achieving a response rate of 33.6%. The study revealed that 65% of participants had limited familiarity or understanding of PG. Over 50% indicated not receiving previous undergraduate or postgraduate training relevant to PG and accordingly their responses to the PG knowledge questions were lacking. Pharmacists with postgraduate training demonstrated better awareness and knowledge. An overwhelming number of participants envisaged carving a role for themselves favouring those that would complement their expertise in medicine management such as recommending appropriate treatment and dosages and suggestions based on PG testing results. Barriers identified were mostly concerning financial cost and shortage of trained staff to support PG services.Conclusions Most surveyed pharmacists were not prepared to deliver PG services and thus require tailored training; nonetheless, they exhibited a positive attitude towards PG suggesting a willingness to bridge learning gaps. This presents an opportunity for relevant organisations to provide necessary training and for universities to enhance the curriculum enabling pharmacists to be involved in PG implementation.